The CMS Silicon Strip Tracker - Pasztor, Gabriella (AIP conference proceedings, 2006)
(CMS Collaboration) The CMS collaboration is constructing the largest silicon tracker ever built with an active silicon area of 200 m2 to provide robust charged particle tracking and vertex reconstruction within the 4T magnetic field of the CMS Solenoid. The design of the detector, the status of the construction and the performance of the substructures are reviewed.